Electrophysiological effects of kappa-opioid analgesic, RU-1205, using machine learning methods - K. Yu. Kalitin; O. Yu. Mukha; A. A. Spasov (Фармация и фармакология (Пятигорск))
The study is focused to the investigation of a new kappa-opioid agonist RU-1205, which exhibits an analgesic effect without causing dysphoric or aversive actions. It is assumed that this effects may be due to its functional selectivity, or the presence of an additional mechanism of action that involves blocking p38 mitogen-activated protein kinase (MAPK).The aim of the study was an experimental identification of RU-1205 mechanisms of action associated with the inhibition of MAPK p38 and functional selectivity for kappa opioid receptors.Materials and methods. The LFP activity was recorded in the male rats weighing 260–280 g (n=62) and implanted with chronic cortical and deep electrodes, after the intracerebroventricular administration of the well-studied reference substances: the selective kappa-opioid agonist U-50488 100 μg; the MAPK p38 blocker SB203580 1 μg; and the investigational compound RU-1205 at 350 μg. The weighted phase lag index (WPLI) was calculated. Subsequently, machine learning methods were employed to reduce the dimensionality and extract connectivity features using the principal component analysis method, then a signal classification was performed (models based on Gaussian processes). Using the local patch-clamp technique in the “whole-cell” configuration, the spike activity of pyramidal neurons in the basolateral amygdala was studied. Neurons were identified by their accommodation properties. After local perfusion of the test compounds, 3 dose-response curves were obtained for: (1) U-50488 at concentrations ranging from 0.001 to 10 μM; (2) combinations of U-50488 (0.001–10 μM) and RU-1205 (10 μM); and (3) the combinations of U-50488 (0.01–10 μM) and RU-1205 (100 μM).Results. The developed models made it possible to classify the compound RU-1205 as a “non-inhibitor” of MAPK p38 with a high probability. The results obtained were confirmed in patch-clamp experiments on acute brain slices where it was demonstrated that U-50488 statistically significantly increases the spike activity of pyramidal neurons of the basolateral amygdala (p <0.05), and RU-1205 interacts with U-50488, competitively suppressing its effect on the spike activity of neurons.Conclusion. The findings suggest that compound RU-1205 displays properties consistent with a functional kappa agonist activity and does not have a significant effect on MAPK p38. The study demonstrates the possibility of integrating electrophysiological measurements and advanced data analysis methods for a deep understanding of drug action and underscores the potential for further research in this area.